Role of aminopeptidase N‐like in the acquisition of begomoviruses by Bemisia tabaci, the whitefly vector - Fan, Yun‐Yun; Chi, Yao; Chen, Na; Cuellar, Wilmer Jose; Wang, Xiao‐Wei (Wiley, 2024)
Sri Lankan cassava mosaic virus (SLCMV) is a prominent causative agent of cassava mosaic disease in Asia and relies on the whitefly Bemisia tabaci cryptic complex for its transmission. However, the molecular mechanisms involved in SLCMV transmission by B. tabaci have yet to be understood. In this study, we identified an aminopeptidase N‐like protein (BtAPN) in B. tabaci Asia II 1, an efficient vector of SLCMV, which is involved in the SLCMV transmission process. Through the use of glutathione S‐transferase pull‐down assay and LC‐MS/MS analysis, we demonstrated the interaction between BtAPN and the coat protein (CP) of SLCMV. This interaction was further confirmed in vitro , and we observed an induction of BtAPN gene expression following SLCMV infection. By interfering with the function of BtAPN, the quantities of SLCMV were significantly reduced in various parts of B. tabaci Asia II 1, including the whole body, midgut, hemolymph, and primary salivary gland. Furthermore, we discovered that BtAPN is conserved in B. tabaci Middle East‐Asia Minor 1 (MEAM1) and interacts with the CP of tomato yellow leaf curl virus (TYLCV), a begomovirus known to cause severe damage to tomato production. Blocking BtAPN with antibody led to a significant reduction in the quantities of TYLCV in whitefly whole body and organs/tissues. These results demonstrate that BtAPN plays a generic role in interacting with the CP of begomoviruses and positively regulates their acquisition by the whitefly.